Outcome after Intravenous Thhrombolysis in patients with Acute Ischemic Stroke - Mallisova, Evagelia; Dokoutsidou, Helen; Kalogianni, Antonia; Vasilopoulos, Georgios (Health & Research Journal, 2019)
Introduction: Vascular disorders represent a major cause of mortality worldwide, with ischemic stroke to be the second cause of mortality, after coronary artery disease. Aim: The aim of the present review was to investigate the contribution of thrombolysis in the outcome of patients with ischemic stroke. Material and Method: This is a systemic review of the literature. The sources of the literature were the databases EBSCO HOST, Elsevier Science Direct, PubMed, Medline, CINAHL, and Google Scholar.No time limit was set. The following keywords were used: ischemic stroke, thrombolysis, infarction, outcome, time window, side effects, benefits, alteplase, etiology, diagnosis, treatment. Results: Three multicenter studies were found to meet the inclusion criteria, the NINDS trial, the ECASS II and the STARS. Thrombolysis in ischemic stroke has been associated with a significantly lower mortality, fewer intracranial hemorrhages and improved neurological outcome when administered in less than 3 hours. Conclusions: The therapeutic benefits of alteplase reduced with time, while it has been determined that after 4.5 hours from the onset of symptoms of ischemic stroke has a significant benefit.